Deaths and disability-adjusted life years of hypertension in China, South Korea, and Japan: A trend over the past 29 years - Qiu, Yan; Ma, Junzhuang; Zhu, Jiahong; Liu, Ying; Ren, Wen; Zhang, Shuaishuai; Ren, Jingjing (Frontiers in Cardiovascular Medicine, 2023)
Background: Hypertension has been confirmed as an independent risk factor for cardiovascular disease and death. Few data were analyzed on deaths and disability-adjusted life years (DALYs) caused by hypertension in East Asia. We aimed to provide an overview of burden attributable to high blood pressure in China in the past 29 years, comparison with those in Japan and South Korea. Methods: Data were collected from 2019 Global Burden of Disease study on diseases due to high systolic blood pressure (SBP). We retrieved the age-standardised mortality rate (ASMR) and disability-adjusted life years (DALYs) rate (ASDR) by gender, age, location and socio-demographic index (SDI). The deaths and DALYs trends were evaluated by estimated annual percentage change, with 95% confidence interval. Findings: Considerable differences were detected in the diseases attributable to high SBP in China, Japan, and South Korea. In 2019, the ASMR and ASDR of diseases due to high SBP in China were 153.34 (126.19, 182.49) per 100,000 population and 2844.27 (2391.91, 3321.12) per 100,000 population respectively, which was about 3.50-fold of those in another two countries. The elders and males had higher ASMR and ASDR in the three countries. Between 1990 and 2019, the declinng trends were less pronounced in China for both the deaths and DALYs. Conclusions: The deaths and DALYs due to hypertension declined in China, Japan and South Korea in the past 29 years, with China having the greatest burden.